Kesulitan Belajar Bahasa Arab Mahasiswa Program Studi Pendidikan Agama Islam Universitas Islam Zainul Hasan Genggong - Yeniati Ulfah; Anyes Lathifatul Insaniyah (Institut Agama Islam Darusssalam Blokagung, 2023)
The result of this study explained and described the difficulties in learning Arabic students experience of Islamic Religious Education study program. The purpose of this study is to find out the learning difficulties and overcome them with several solutions provided by researchers. The data collection was collected with observation and interview. The data analysis arranged from reduction data, presentation data and conclusions. The results of this study explained that the factor of difficulties of learning Arabic are lack of motivation and interest in learning Arabic, minimal Arabic vocabulary mastery, there is no inenvironment to support Arabic Learning by writing and orally, and there is difficulty in applaying nahwu and sharraf learning.